Studies of ternary systems of sulfadiazine with β-cyclodextrin and aminoacids - Alicia Delrivo; Ariana Zoppi; Gladys Granero; Marcela Longhi (Facultad de Farmacia, Universidad de Granada, 2016)
Introduction: Cyclodextrins (CD), are known to form inclusion complexes with a variety of guest molecules both in solution and in the solid state. This can lead to the alteration of properties of guest molecules. Unfortunately, the complexation efficiency of CD is rather low, and can be enhanced by formation of ternary complexes using aminoacids (AA). Sulfadiazine (SDZ) is an antibiotic with extremely low water solubility which limits its therapeutic applications and bioavailability. Objetives: The aim of this work was to increase the aqueous solubility of SDZ by preparing ternary complexes of this drug with β-cyclodextrin (βCD) and an AA as a third auxiliary substance. Materials y Methods: Complex formation was studied by phase solubility analysis (PSA), nuclear magnetic resonance (NMR), differential scanning calorimetry (DSC), thermogravimetric analysis (TG) and scanning electron microscopy (SEM). Results: The apparent stability constants (K C) of the multicomponent complexes were calculated from the solubility diagrams. By the analysis of the NMR spectra, it could be said that the shifts of some protons evidenced the important role of the AA in the formation of multicomponent complexes. Among the AA, Arginine (ARG) proved to have better solubilizing properties for SDZ, reaching an improvement up to 70 times. The use of DSC, TG and SEM suggested the formation of new solid phases between SDZ:βCD:AA. Conclusions: As a result of this research, it was determined that ternary products were more effective in improving drug solubility than the corresponding SDZ:βCD binary system.